Unusual Presentation of Brain Tumor in a Child A Case Report - Mahmoud Alhandi Omar Helal (16685388) (2023)
The most popular type of neurological tumor in childhood is medulloblastoma, which is the most malignant neoplasm of the posterior fossa and cerebellum. Central nervous system neoplasms can cause symptoms and signs due to local invasion, compression of normal structures, and increased intracranial pressure by either a mass effect or obstruction of cerebrospinal fluid flow, resulting in hydrocephalus. Usually, headache is the most common symptom of central nervous system tumors, and the median duration between symptoms beginning and diagnosis of brain tumors in children ranges from 2.5 to 3.5 months. Furthermore, several predisposing factors for brain tumors have been identified such as Epstein–Barr virus infection, exposure to ionizing radiation, and inherited diseases. Recently, the advances in diagnosis and treatment have improved the survival of many children with neurological neoplasms. However, this therapy is associated with long-term complications, and its prognosis remains poor. We present the case of a 4-year-old girl with adequate neuropsychomotor development who presented to the pediatric emergency center with a 14-day history of headache, which was prominent in the morning, neck, back, and bilateral leg pain two days prior to presentation. Brain and Spine Magnetic resonance imaging revealed a cerebellar mass lesion in the posterior fossa. The patient underwent surgery, followed by histopathological and immunohistochemical staining. This case is considered rare and distinctive because the symptoms included only headache for two weeks, no impaired vision, no vomiting, no mental disorders, no abnormal gait, and no ataxia or body imbalance. We report this case to focus on the features of the manifestation and hence increase the chances of timely diagnosis in the future. Consequently, the probability of central nervous system tumors should always be considered in children with headache, and they must be under regular follow-up for early diagnosis and treatment. Other Information Published in: American Journal of Pediatrics License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://doi.org/10.11648/j.ajp.20230902.12